Consider a bead on a circle of radius The bead starts moving along the circle with velocity subject to a friction force opposite to its velocity. The magnitude of the friction force is where is the normal force on the trajectory and .
After it finishes the first complete circle, the velocity of the bead is
What is the ratio
Neglect the effect of gravity.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will measure the distance x along the circular path of the bead. The normal force is the centripetal force, m v 2 / R , and the equation of motion along the circular path is
m d t d v = − μ m R v 2
We will use d t d v = d x d v d t d x = v d x d v , and we get
d x d v = − v R μ
The solution of this differential equation is v = v 0 e − μ x / R , satisfying the initial condition of v = v 0 at x = 0 . After the first circle is completed we have x = 2 π R and we get
v 0 v ′ = e − 2 π μ = 0 . 2 8 4 6